Structure‐Independent Conductance of Thiophene‐Based Single‐Stacking Junctions. (16th January 2020) - Li, Xiaohui; Wu, Qingqing; Bai, Jie; Hou, Songjun; Jiang, Wenlin; Tang, Chun; Song, Hang; Huang, Xiaojuan; Zheng, Jueting; Yang, Yang; Liu, Junyang; Hu, Yong; et al.
Abstract: The experimental investigation of intermolecular charge transport in π‐conjugated materials is challenging. Herein, we describe the investigation of charge transport through intermolecular and intramolecular paths in single‐molecule and single‐stacking thiophene junctions by the mechanically controllable break junction (MCBJ) technique. We found that the ability for intermolecular charge transport through different single‐stacking junctions was approximately independent of the molecular structure, which contrasts with the strong length dependence of conductance in single‐molecule junctions with the same building blocks, and the dominant charge‐transport path of molecules with two anchors transited from an intramolecular to an intermolecular path when the degree of conjugation increased. An increase in conjugation further led to higher binding probability owing to the variation in binding energies, as supported by DFT calculations. Abstract : Welcher Transportweg? Die Leitfähigkeit von Thiophen‐basierten Einzelstapel‐Junctions ist nahezu unabhängig vom Konjugationsmuster der Molekülstruktur. Mit zunehmender Länge des konjugierten Abschnitts kam es zu einem Wechsel des dominanten Ladungstransportweges von intramolekular zu intermolekular (siehe Bild).